THE CONTRIBUTION OF MUSLIM SCIENTISTS TO THE DEVELOPMENT OF MODERN SCIENCE - Komaruddin, Muhammad (Jurnal Konseling Pendidikan Islam, 2023)
This paper presents a discussion of the contribution of Muslim scientists to the development of modern science. It is commonly known that during the golden age of Islam, scientists emerged who were very competent in their respective fields. They succeeded in appearing as philosophers and scientists who filled various scientific fields, such as medicine, mathematics, chemistry, physics and so on. Their knowledge is very valuable, especially for the development of science in the following times. So valuable is science and what it offers, that it is not uncommon for scientists who came later to call them the fathers of science in their respective fields. However, not all of them will be discussed in this paper, but only the triumvirate of Muslim scientists, namely Ibn Rushd, Ibn al-Haytham, and Jabir ibn Hayyan. The contributions of the three were enormous to the development of modern science and are recognized by scientists, both in the East and especially in the West.